Method for preparing multi-scale reinforced carbon aerogel composite material by reducing carbonization shrinkage rate under assistance of expansible graphite
By introducing expandable graphite into the carbon aerogel composite material, combined with the impregnation and high-temperature annealing treatment of PAN-based fiber felt, the problem of high carbonization shrinkage is solved, and the preparation of a lightweight, high-strength, heat insulation-load integrated multi-scale enhanced carbon aerogel composite material is achieved.
Patent Information
- Application Number
- CN202411349825.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-28
AI Technical Summary
During the high carbonization shrinkage process, carbon aerogel composite materials cause debonding and cracks to occur during high-temperature annealing, which affects its mechanical and thermal insulation properties.
Expandable graphite assisted preparation of multi-scale reinforced carbon aerogel composite materials. By mixing phenolic resin with expandable graphite, combined with impregnation of PAN-based preoxidized fiber mat and high-temperature annealing treatment, carbon aerogel matrix construction and in-situ expansion of expandable graphite are achieved.
It effectively suppresses the carbonization shrinkage rate, improves the mechanical strength and high-temperature thermal insulation performance of the material, and has a simple, cost-effective process, suitable for large-size preparation and mass production.
Smart Images

Figure CN119528599A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature thermal insulation materials, and in particular to a method for preparing a multi-scale reinforced carbon aerogel composite material by using expandable graphite to assist in reducing carbonization shrinkage, and use of the composite material in the field of high-temperature thermal insulation. Background Art
[0002] Aerogel materials are ultra-lightweight materials formed by filling gaseous dispersion media in a nanoporous network skeleton. The nanoscale pores and three-dimensional network structure give them ultra-low thermal conductivity, and they are a hot topic in the field of thermal insulation materials. Since carbon aerogel was prepared by Pekala et al. in 1989 through the cracking of resorcinol-formaldehyde organic aerogel, it has attracted extensive research at home and abroad. Due to its low density, low thermal conductivity and high specific extinction coefficient, carbon aerogel can still maintain its mesoporous structure in an ultra-high temperature environment of 2800°C under an inert atmosphere. It is one of the ultra-high temperature insulation materials with great application potential in thermal protection systems in the aerospace field. However, the highly developed pore structure and rigid carbon skeleton of carbon aerogel lead to its inherent brittleness and low mechanical strength. Large-scale preparation is prone to cracking, which seriously limits its practical application.
[0003] In order to improve the mechanical properties of carbon aerogel, reinforcements are usually added to prepare carbon aerogel composites. Currently, commonly used reinforcements include fibers, carbon nanotubes, graphene, etc. Among them, fiber reinforcements have become one of the main reinforcements for carbon aerogels due to their high aspect ratio, excellent strength, and easy textile molding. Although rigid fiber reinforcements such as carbon fibers and ceramic fibers can significantly improve the mechanical properties of the material, due to the mismatch in shrinkage between the carbon aerogel organic precursor and the fiber during high-temperature annealing, it is easy to cause matrix debonding and cracking, and ultimately affect the mechanical and thermal insulation properties of the composite material.
[0004] In contrast, the organic precursor fibers can shrink synergistically with the organic precursors of the carbon aerogel during high-temperature annealing, thereby effectively avoiding the generation of matrix cracks. However, the shrinkage rate of the organic precursor during the carbonization process often reaches more than 30%, and the size span between the large-scale fibers and the nanoscale carbon aerogel matrix is large, resulting in excessive density of the composite material and an unsatisfactory pore structure, making it difficult to take into account both mechanical and thermal insulation properties. Therefore, it is urgent to explore new preparation methods for carbon aerogel composites under large-scale, atmospheric pressure drying preparation conditions to inhibit the carbonization shrinkage rate of the composite material and maintain the stability of the material's microstructure, so as to synergistically improve the mechanical strength and ultra-high temperature thermal insulation properties of carbon aerogel composites. Summary of the invention
[0005] The purpose of the present invention is to provide a new method for preparing multi-scale reinforced carbon aerogel composite materials based on expandable graphite, which can realize large-scale preparation of lightweight, high-strength thermal insulation-load-bearing integrated multi-scale reinforced carbon aerogel composite materials under simple, economical and efficient process conditions.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a multi-scale reinforced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite, comprising the following steps:
[0008] (1) adding commercial phenolic resin PR to a solvent, stirring and mixing thoroughly, then adding expandable graphite EG thereto, continuing to stir until evenly dispersed, and finally adding a curing agent, stirring and mixing thoroughly until evenly mixed, to obtain a precursor impregnation solution;
[0009] (2) placing the polyacrylonitrile (PAN)-based pre-oxidized fiber felt into a mold, placing it in a vacuum impregnation machine for vacuum treatment, and exhausting the air inside the felt body; then, using the negative pressure effect, slowly injecting the precursor impregnation liquid prepared in step (1), and after sufficient impregnation, taking out the sample together with the mold to obtain an impregnated PAN felt body;
[0010] (3) transferring the impregnated PAN felt to a vacuum drying oven and curing it at 60-120° C. for 12-36 hours under a vacuum environment, and after the impregnation liquid inside the felt is completely cured to obtain a yellow block sample, continuing to dry it at 80-200° C. for 8-24 hours to obtain a dried PAN / EG-PR aerogel composite material;
[0011] (4) placing the dried PAN / EG-PR aerogel composite material obtained in step (3) in a high-temperature tubular furnace and performing high-temperature annealing treatment under the protection of an inert atmosphere to completely carbonize the PAN-based pre-oxidized fiber felt and the PR aerogel, and finally obtaining a carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material, denoted as Cf / EG-CAs.
[0012] Furthermore, the phenolic resin is a liquid phenolic resin with a solid content greater than 75%, and the expandable graphite is flake graphite with a particle size of 50-300 meshes, an expansion multiple of 50-200 times, and intercalation acidification treatment.
[0013] Furthermore, in step (1), the solvent is ethylene glycol, and the curing agent is one of sodium carbonate, sodium bicarbonate, hexamethylenetetramine, vinyl acetate and ammonium chloride.
[0014] Furthermore, in step (1), the mass ratio of PR to solvent is 1:2-6, EG accounts for 0.5-5.0wt.% of the total mass of PR and solvent, and the curing agent accounts for 2-8wt.% of the total mass of PR and solvent.
[0015] Furthermore, in step (2), the vacuum treatment time is 20 to 120 minutes, the injection rate of the precursor impregnation solution is 1 to 5 mL / min, and the impregnation time is 1 to 4 hours.
[0016] Furthermore, in step (4), the inert atmosphere is high-purity nitrogen or high-purity argon, and the high-temperature annealing treatment is carried out at 700-1200°C for 10-60 minutes. Furthermore, the flow rate of the protective atmosphere is 0.005-10L / min, the heating rate of the insulation program is 1-5°C / min, and the cooling rate is 5-10°C / min.
[0017] The present invention also provides a carbon aerogel composite material prepared by the above method and synergistically reinforced with carbon fiber felt and expandable graphite, wherein the matrix is a phenolic resin-based carbon aerogel, the large-scale reinforcement is a PAN-based carbon fiber felt, and the medium-scale reinforcement is expandable graphite.
[0018] The present invention further provides use of the multi-scale reinforced carbon aerogel composite material as a high-temperature thermal insulation material.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0020] (1) The method provided by the present invention is a method for preparing a multi-scale reinforced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite. The method uses a phenolic resin as a matrix, and after being melted into an expandable graphite reinforcement, an impregnation liquid is prepared. The PAN-based pre-oxidized fiber felt is vacuum impregnated. After curing and drying, the carbon aerogel matrix is constructed, the PAN fiber felt is carbonized, and the in-situ expansion of the expandable graphite is achieved in one step under high-temperature annealing conditions, thereby preparing a low-shrinkage, light-weight, high-strength heat-insulating-load-bearing integrated carbon aerogel composite material. The process of the present invention is simple and easy to operate, does not require a special freezing or supercritical drying device, is economical and efficient, and is suitable for large-scale preparation and mass production.
[0021] (2) The present invention proposes to introduce medium-scale expandable graphite reinforcement into the large-scale carbon fiber reinforcement and the small-scale carbon aerogel matrix. On the one hand, it acts as a bridging material to form multi-scale reinforcement and improve the stability of the composite material. On the other hand, the in-situ high-rate expansion of expandable graphite at the carbonization temperature of the composite material is utilized to inhibit the carbonization shrinkage of the organic precursor and the organic fiber felt, maintain the stability of the composite structure, improve the porosity of the composite material, and synergistically improve the thermal insulation and mechanical properties of the composite material, thereby preparing a thermal insulation-load-bearing integrated carbon aerogel composite material.
[0022] (3) The preparation method provided by the present invention, wherein the expandable graphite can expand at a certain temperature and form a porous network structure with the phenolic resin, which can effectively inhibit the heat conduction and heat convection of the air, thereby significantly improving the thermal insulation effect of the multi-scale carbon aerogel composite material. The addition of expandable graphite makes the combination between the carbon aerogel matrix and the large-scale carbon fiber reinforcement more compact, not easy to debond, so that the composite material can maintain good thermal stability and chemical stability in a high-temperature heat insulation environment.
[0023] (4) The method for preparing carbon aerogel composite materials by using expandable graphite to assist in reducing carbonization shrinkage provided by the present invention utilizes the high-temperature in-situ expansion of expandable graphite to inhibit the carbonization shrinkage of organic precursors. The method is suitable for the application of preparing carbon aerogel composite materials from most organic precursors. The method does not involve any complicated processing steps and is very simple, economical and efficient. The method is suitable for large-scale synthesis of carbon aerogel composite materials and has industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0025] Figure 1 The present invention provides a schematic flow chart of a method for preparing a multi-scale reinforced carbon aerogel composite material by using expandable graphite to assist in reducing carbonization shrinkage, as provided in an embodiment of the present invention.
[0026] Figure 2 These are optical photographs of the multi-scale reinforced carbon aerogel composite materials prepared in Examples 1-3 and the carbon fiber reinforced carbon aerogel composite materials prepared in Comparative Example 1, wherein Figures ac correspond to Examples 1-3, respectively, and Figure d corresponds to Comparative Example 1.
[0027] Figure 3 The scanning electron microscope images are of the multi-scale reinforced carbon aerogel composite materials prepared in Examples 1-3 and the carbon fiber reinforced carbon aerogel composite materials prepared in Comparative Example 1, wherein Figures (a)-(c) correspond to Examples 1-3, respectively, and Figure (d) corresponds to Comparative Example 1.
[0028] Figure 4 This is a comparison chart of the volume shrinkage of the multi-scale reinforced carbon aerogel composite materials prepared in Examples 1-3 and the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1 before and after carbonization.
[0029] Figure 5X-ray diffraction patterns of the multi-scale reinforced carbon aerogel composite material prepared in Example 3 and the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1.
[0030] Figure 6 The stress-strain curve of the compressive strength test of the multi-scale reinforced carbon aerogel composite material prepared in Example 3 using an electronic universal testing machine.
[0031] Figure 7 This is a comparison chart of thermal conductivity of the multi-scale reinforced carbon aerogel composite material prepared in Example 3 and the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1 from room temperature to 1100° C. measured by a laser thermal conductivity meter. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This example prepares a carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material according to the following steps:
[0035] (1) 40 g of a commercial phenolic resin with a solid content of 75% and 80 g of ethylene glycol were stirred evenly and fully mixed in a mass ratio of 1:2, and then 1.2 g (1 wt.%) of expandable graphite with a 200 mesh and an expansion ratio of 40 times was added, and the mixture was stirred until uniformly dispersed; then 4.8 g (4 wt.%) of hexamethyltetramine was added, and the mixture was stirred evenly to obtain a precursor impregnation solution.
[0036] (2) Place a φ4×1 cm PAN-based pre-oxidized fiber felt into a mold and place it in a vacuum impregnation machine for 120 min to exhaust the air inside the felt. Then, using negative pressure, slowly inject the precursor impregnation solution prepared in step (1) at an injection rate of 3 mL / min. After fully impregnating for 2 h, take out the sample together with the mold to obtain an impregnated PAN felt.
[0037] (3) The impregnated PAN felt was transferred to a vacuum drying oven and cured at 80°C for 20 h under vacuum. The sample changed from reddish brown to yellow blocks. The sample was dried at 120°C for about 12 h until the weight of the sample did not change, thereby obtaining a dried PAN / EG-PR aerogel composite material.
[0038] (4) placing the composite material obtained in step (3) into a graphite boat, placing it into a high-temperature tubular furnace, using high-purity nitrogen with a flow rate of 5 L / min as a protective gas, heating from room temperature to 900° C. at a rate of 5° C. / min, and keeping the temperature for 30 min, and then cooling to room temperature at a rate of 5° C. / min, thereby obtaining a carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material.
[0039] Example 2
[0040] In this example, a carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material was prepared according to the same steps and conditions as in Example 1, except that the expansion ratio of the expandable graphite used was 60 times.
[0041] Example 3
[0042] In this example, a carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material was prepared according to the same steps and conditions as in Example 1, except that the expansion ratio of the expandable graphite used was 60 times and the added amount was 6 g (5 wt.%).
[0043] Comparative Example 1
[0044] In this comparative example, a carbon fiber reinforced carbon aerogel composite material was prepared according to the same steps and conditions as in Example 1, except that the amount of expandable graphite added was 0.
[0045] Morphology observation and performance testing:
[0046] The carbon aerogel composite materials prepared in Examples 1-3 of the present invention and Comparative Example 1 were subjected to morphological observation and performance testing, and the following results were obtained:
[0047] (1) Figure 2 The optical photographs of the prepared carbon aerogel composite materials, wherein: Figures ac are respectively multi-scale reinforced carbon aerogel composite materials prepared by adding expandable graphite with different mass concentrations and expansion multiples in Examples 1-3; Figure d is a carbon fiber reinforced aerogel composite material without expandable graphite prepared in Comparative Example 1.
[0048] Depend on Figure 2 It can be seen that the macroscopic size of the carbon fiber / expandable graphite multi-scale reinforced carbon aerogel composite material prepared in Examples 1-3 is significantly larger than that of the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1, indicating that the addition of expandable graphite can effectively suppress the carbonization shrinkage of the composite material and obtain a multi-scale reinforced composite material with a more stable network structure. At the same time, with the increase of the mass concentration and expansion ratio of the expandable graphite added in Examples 1-3, the macroscopic size of the multi-scale reinforced carbon aerogel composite material also gradually increases, indicating that the added expandable graphite has a significant effect on the carbonization shrinkage of the composite material.
[0049] (2) Figure 3 The scanning electron microscope images of the carbon aerogel composite materials prepared in Examples 1-3 and Comparative Example 1 are shown, wherein: Figure 3 (a)-(c) are scanning electron microscope photos of the multi-scale reinforced carbon aerogel composite materials prepared in Examples 1-3 at a magnification of 5k; Figure 3 (d) is a scanning electron microscope image of the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1 at a magnification of 5k.
[0050] Depend on Figure 3 It can be seen that after adding expandable graphite reinforcement, the carbon aerogel matrix and expandable graphite form a network structure, which is more tightly coated on the surface of carbon fiber. As the expansion multiple increases and the amount of expandable graphite added increases, the bonding force between the carbon fiber and the matrix becomes stronger, and the matrix coating becomes denser.
[0051] (3) Figure 4 This is a comparison chart of the volume shrinkage rates of the carbon aerogel composite materials prepared in Examples 1-3 and Comparative Example 1 before and after carbonization, calculated using the shrinkage rate calculation formula.
[0052] Due to the addition of expandable graphite reinforcement, the multi-scale reinforced carbon aerogel composites prepared in Examples 1-3 have significantly reduced shrinkage compared to the carbon fiber reinforced carbon aerogel composites prepared without the addition of expandable graphite in Comparative Example 1. Among them, compared with Comparative Example 1, the volume shrinkage of Example 3 is reduced from 46% to 27%, proving that with the increase of expandable graphite content and expansion multiple, expandable graphite expands in situ and bridges the carbon aerogel matrix and the carbon fiber, inhibiting the carbonization shrinkage of the organic precursor and forming a stable multi-scale three-dimensional network structure.
[0053] (4) Figure 5 X-ray diffraction (XRD) patterns of the carbon aerogel composite materials prepared in Example 3 and Comparative Example 1.
[0054] XRD results show that the multi-scale reinforced carbon aerogel composite material prepared in Example 3 of the present invention and the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1 are both carbon-based materials.
[0055] (5) Figure 6 This is a compressive stress-strain curve of the multi-scale reinforced carbon aerogel composite material prepared in Example 3.
[0056] The compressive strength of the multi-scale reinforced carbon aerogel composite material prepared in Example 3 of the present invention can reach up to 64.831 MPa, indicating that the multi-scale three-dimensional network structure constructed by carbon fiber, expandable graphite and carbon aerogel matrix has good mechanical strength.
[0057] (6) Figure 7The thermal conductivity curves of the carbon aerogel composite materials prepared in Example 3 of the present invention and Comparative Example 1 from room temperature to 1100°C.
[0058] The multi-scale reinforced carbon aerogel composite material prepared in Example 3 of the present invention has low thermal conductivity at room temperature and high temperature of 1100°C, which are 0.092 and 0.357 W / m·K respectively; while the thermal conductivity of the carbon fiber reinforced carbon aerogel composite material prepared in Comparative Example 1 is significantly higher than that of Example 3. This indicates that the addition of expandable graphite reinforcement can inhibit the carbonization shrinkage of the organic precursor and maintain the porous network structure of the aerogel material, thereby reducing the thermal conductivity and improving its thermal insulation performance.
[0059] In summary, it can be seen that the method of the present invention not only has a simple preparation process, a controllable reaction process, low cost, and easy scale-up preparation, but also the prepared multi-scale reinforced carbon aerogel composite material has a good three-dimensional network structure, a high degree of cross-linking between the matrix and the reinforcement, and a stable structure. Therefore, it has both good mechanical strength and high-temperature thermal insulation properties.
[0060] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as.
Claims
1. A method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite, characterized in that: The steps include: (1) fully mixing phenolic resin PR and expandable graphite in a solvent, and adding a curing agent to prepare a precursor impregnation solution; (2) subjecting the polyacrylonitrile (PAN)-based pre-oxidized fiber felt to a vacuum treatment in a vacuum impregnator, and then injecting the precursor impregnation solution obtained in step (1) into the felt under negative pressure to fully impregnate the felt, thereby obtaining an impregnated PAN felt body; (3) curing and drying the impregnated PAN felt under vacuum conditions to obtain a dried PAN / EG-PR aerogel composite material; (4) The dried PAN / EG-PR aerogel composite material obtained in step (3) is subjected to high temperature annealing treatment under inert atmosphere protection to obtain a multi-scale reinforced carbon aerogel composite material, which is denoted as Cf / EG-CAs.
2. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: The matrix of the multi-scale reinforced carbon aerogel composite material is phenolic resin-based carbon aerogel, the large-scale reinforcement is PAN-based carbon fiber felt, and the medium-scale reinforcement is expandable graphite.
3. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (1), the phenolic resin is a liquid phenolic resin with a solid content greater than 75%, and the expandable graphite is flake graphite with a particle size of 50-300 meshes, an expansion multiple of 50-200 times, and intercalated acid-treated.
4. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (1), the solvent is ethylene glycol, and the curing agent is one of sodium carbonate, sodium bicarbonate, hexamethylenetetramine, vinyl acetate and ammonium chloride.
5. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (1), the mass ratio of PR to solvent is 1:2-6, EG accounts for 0.5-5.0wt.% of the total mass of PR and solvent, and the curing agent accounts for 2-8wt.% of the total mass of PR and solvent.
6. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (2), the vacuum treatment time is 20 to 120 minutes, the injection rate of the precursor impregnation solution is 1 to 5 mL / min, and the impregnation time is 1 to 4 hours.
7. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (3), the constant temperature curing temperature is 60-120°C, the curing time is 12-36h, and the drying temperature is 80-200°C, and the drying time is 8-24h.
8. The method for preparing a multi-scale enhanced carbon aerogel composite material by reducing carbonization shrinkage with the aid of expandable graphite according to claim 1, characterized in that: In step (4), the inert atmosphere is high-purity nitrogen or high-purity argon, and the high-temperature annealing treatment is carried out at 700-1200° C. for 10-60 minutes.
9. A multi-scale reinforced carbon aerogel composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the multi-scale reinforced carbon aerogel composite material according to claim 9 as a high-temperature thermal insulation material.
Citation Information
Cited By
Carbon / carbon composite aerogel based on congruent resin coating and preparation method
CN120479316A